What Makes a Customer Brand Citizen in Restaurant Industry - Han, Hua; Yang, Yi-Chun; Kuang, Tingyue; Song, Hemin (Frontiers in Psychology, 2022)
Due to the crucial role of customers’ brand citizenship behaviors on brand strength, this study explored the relationship between brand uniqueness, brand credibility, brand intimacy, brand love, and brand citizenship behavior in Taiwan’s restaurant context. The objects are the customers of Wang Steak, a famous restaurant chain in Taiwan. A total of 358 valid responses were gathered from a questionnaire survey, with a response rate of 71.6%. We used structural equations modeling to analyze the data. Brand uniqueness, brand credibility, and brand intimacy all have a positive relationship with brand love. Moreover, brand love was positively associated with brand citizenship behavior. The ﬁndings provide greater insights into the relationship of perceived brand uniqueness, brand credibility, brand intimacy, and brand love with customers’ brand citizenship behaviors.